2018
DOI: 10.1111/jne.12659
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of central and peripheral circadian clocks in energy metabolism regulation

Abstract: Metabolic health founds on a homeostatic balance that has to integrate the daily changes of rest/activity and feeding/fasting cycles. A network of endogenous 24‐hour circadian clocks helps to anticipate daily recurring events and adjust physiology and behavioural functions accordingly. Circadian clocks are self‐sustained cellular oscillators based on a set of clock genes/proteins organised in interlocked transcriptional‐translational feedback loops. The body's clocks need to be regularly reset and synchronised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 110 publications
(259 reference statements)
0
19
0
2
Order By: Relevance
“…Loss of the SCN pacemaker, for example by surgical lesioning, in mice causes a gradual desynchronization of rhythmicity in peripheral tissues. In rats with ablated SCN, the normal diurnal adrenal corticosterone rhythm is no longer detectable (Kolbe et al 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Loss of the SCN pacemaker, for example by surgical lesioning, in mice causes a gradual desynchronization of rhythmicity in peripheral tissues. In rats with ablated SCN, the normal diurnal adrenal corticosterone rhythm is no longer detectable (Kolbe et al 2018).…”
Section: Introductionmentioning
confidence: 96%
“…There are obvious circadian rhythmic changes in the process of maintaining homeostasis and adapting to the external environment [1]. The circadian rhythm refers to an approximately 24 h biological rhythm produced by the endogenous circadian oscillator [2]. The central pacemaker of this rhythm is located in the suprachiasmatic nucleus (SCN) of the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to rodents (Peripheral clocks control cell and organ physiology: lessons from rodent studies), also in human individuals there is accumulating evidence that metabolic, cardiovascular, endocrine, digestive, and immune functions follow diurnal rhythms (Fig. 3) [47,222,224,225,227,228,281,[369][370][371][372][373]375]. Although molecular clock studies in humans stay a challenging endeavor, analyses conducted in human saliva, serum, and urine serial samples obtained across 24 h revealed that large number of metabolites exhibits circadian rhythmic profiles [143,221,[376][377][378].…”
Section: The Circadian Clock System and Human Diseasesmentioning
confidence: 99%